Dexamethasone, Remdesivir and Azithromycin modulate ACE2 and IL-6 in Lung Epithelial Cells - Ulrich-Merzenich, Gudrun Sigrid; Shcherbakova, Anastasiia; Pizarro, Carmen; Skowasch, Dirk (Pneumologie, 2024)
Background The optimal use of steroids in COVID-19 patients remains challenging. Current S3-guidelines “Recommendations for patients with COVID-19” recommend dexamethasone (DEX) for patients requiring respiratory support, remdesivir (RD) in the early disease phase and azythromycin (AZ) is no longer recommended. We investigated effects of DEX, RD and AZ in a lipopolysaccharide induced inflammation in lung cells in vitro and analyzed publicly available datasets with a focus on the Angiotensin-converting enzyme 2 (ACE2) to better understand drugs’ mechanisms of action.Methods human bronchial (Calu) and alveolar (A549) lung epithelial cells were treated with DEX, AZ or RDV in the presence of lipopolysaccharides (LPS). Gene expression (GE) of ACE2, IL-6 and the IL-6 protein release were measured. Publicly available GE data from lung tissues of COVID-19 patients and from lung cells treated with DEX were analyzed for the GE of ACE2.Results DEX increased and RDV and AZ reduced the GE of ACE2 in LPS-stimulated bronchial and alveolar epithelial cells. Only DEX significantly reduced LPS-induced IL-6 releases in alveolar cells substantially. The database analyses showed an, albeit not always significant, increase in ACE2 for lung tissue or cell lines treated with DEX. Lung tissue from patients after COVID-19 infection as well as bronchial cell cultures after COVID-19 infection showed lower GEs of ACE2.Discussion and Conclusion DEX can increase ACE2 expression in vitro and thereby the portal of entry of SARS-CoV-2 into lung cells during an LPS induced inflammation. Simultaneously the inflammatory marker IL-6 is reduced. Comparative database analyses indicate that these processes can also take place in vivo.
Keywords: SARS-CoV-2 infection; ACE2 expression; alveolar epithelial cells; IL-6; LPS